ETNOSENTRISME, STEREOTIP DAN PRASANGKA DI KALANGAN KARYAWAN ETNIS JAWA DAN TIONGHOA DI KOTA SURAKARTA - Amanda, Agnes (Transformasi, 2017)
The purpose of this study was to describe how ethnocentrism, stereotypes and prejudices thatdevelop among the workers (employees) Javanese and Chinese in Surakarta. Howethnocentrism, stereotypes and prejudices influence in communication. This research isqualitative descriptive case study approach. Data collection technique used in-depthinterview and FGD (Focus Group Discussion). The Uncertainty Reduction Theory candescribe the results of this study. People with different ethnicities looking for informationabout other to reduce uncertainty before they make communication. They use the informationto predict the behavior of others. The study also shows that the development ofcommunication that ensue does not depend on ethnicity but depends on the personalcharacter and attitude. Stereotypes and prejudices that people get in beginning will be changewith the more knowledge and relation.Key words: ethnocentrism, stereotypes, prejudices, intercultural communication